Complications and Resource Use Associated With Surgery for Chiari Malformation Type 1 in Adults: A Population Perspective. Issue 2 (23rd April 2015) - Greenberg, Jacob K.; Ladner, Travis R.; Olsen, Margaret A.; Shannon, Chevis N.; Liu, Jingxia; Yarbrough, Chester K.; Piccirillo, Jay F.; Wellons, John C.; Smyth, Matthew D.; Park, Tae Sung; Limbrick, David D.
Abstract: BACKGROUND: Outcomes research on Chiari malformation type 1 (CM-1) is impeded by a reliance on small, single-center cohorts. OBJECTIVE: To study the complications and resource use associated with adult CM-1 surgery using administrative data. METHODS: We used a recently validated International Classification of Diseases, Ninth Revision, Clinical Modification code algorithm to retrospectively study adult CM-1 surgeries from 2004 to 2010 in California, Florida, and New York using State Inpatient Databases. Outcomes included complications and resource use within 30 and 90 days of treatment. We used multivariable logistic regression to identify risk factors for morbidity and negative binomial models to determine risk-adjusted costs. RESULTS: We identified 1947 CM-1 operations. Surgical complications were more common than medical complications at both 30 days (14.3% vs 4.4%) and 90 days (18.7% vs 5.0%) postoperatively. Certain comorbidities were associated with increased morbidity; for example, hydrocephalus increased the risk for surgical (odds ratio [OR] = 4.51) and medical (OR = 3.98) complications. Medical but not surgical complications were also more common in older patients (OR = 5.57 for oldest vs youngest age category) and male patients (OR = 3.19). Risk-adjusted hospital costs were 22530 at 30 days and 24852 at 90 days postoperatively. Risk-adjusted 90-day costs were more than twice as high for patients experiencing surgical (46264) or medical (65679) complications than for patients without complications (18880). CONCLUSION: Complications after CM-1 surgery are common, and surgical complications are more frequent than medical complications. Certain comorbidities and demographic characteristics are associated with increased risk for complications. Beyond harming patients, complications are also associated with substantially higher hospital costs. These results may help guide patient management and inform decision making for patients considering surgery.